Consequences of early postnatal benzodiazepines exposure in rats. II. Social behavior - Mikulecká, Anna; Šubrt, Martin; Pařízková, Martina; Mareš, Pavel; Kubová, Hana (Frontiers in Behavioral Neuroscience, 2014)
Social behavior represents an integral part of behavioral repertoire of rats particularly sensitive to pharmacological and environmental influences. The aim of the present study was to investigate whether early postnatal clonazepam (CZP) exposure can induce age-dependent changes related to expression of social behavior. The drug was administered from postnatal day (P) 7 until P11 at daily doses of 0.1, 0.5 and 1.0 mg/kg i.p. We designed three experiments to assess whether exposure to CZP affects social behavior in respect to the age of rats and the test circumstances, specifically their familiarity with test conditions during adolescence (P32), social behavior in juveniles and adolescents (P18-P42) and social behavior in a resident-intruder paradigm. The frequency and duration of a various patterns of social behavior related to play and social investigation not related to play were evaluated. The results showed that CZP postnatal exposure decreased social play behavior regardless of age and familiarity or unfamiliarity of experimental environment but did not affect the social investigation per se. When rats were confronted with an intruder in their home cages intense wrestling and inhibition of genital investigation were found. In conclusion, these findings show that short-term CZP postnatal exposure inhibits social play behavior and alters specific patterns of social behavior in an age and environment related manner